The Loose Parts Media from Recycled Materials to Early Childhood Creativity - Ni Wayan Widiari; Didith Pramunditya Ambara; Rendy Setyowahyudi (Universitas Pendidikan Ganesha, 2026)
Learning in Early Childhood Education is still dominated by the use of conventional learning media that are structured and teacher-centered, resulting in limited opportunities for children to explore and develop their creativity. This condition affects children’s low ability to express ideas, use imagination, and produce independent and original works. This study aims to examine the effect of using loose parts media made from recycled materials on enhancing early childhood creativity. This research employed a quantitative approach with a quasi-experimental design using a one-group pretest–posttest model. The participants were early childhood children in Group B who were involved in the learning process during the current academic year. Data were collected through observation using a creativity assessment sheet based on indicators of fluency, flexibility, originality, and elaboration. The data were analyzed using prerequisite tests, namely normality and homogeneity tests, followed by a t-test with the assistance of statistical software. The results of the study indicate an improvement in children’s creativity after being treated with the use of loose parts media from recycled materials. These findings suggest that the media is effective in providing broader opportunities for children to explore, create, and produce independent works. In addition, the use of this media also provides educational value in fostering environmental awareness and encouraging the habit of creatively utilizing waste materials from an early age. The implication of this study highlights the importance of innovative learning media in early childhood education that are more flexible, contextual, and exploration-based to optimally support children’s creative development.